Analysis of Employee Work Motivation at BAPPEDA Sleman District - Guntur Andi; Nadia Azkal Uyun; Herlina Nur Rahma Sari (International Journal of Economic and Tourism Research, 2025)
Employee motivation is a critical determinant of organizational effectiveness, particularly in public sector institutions such as BAPPEDA Sleman. This study examines the factors influencing employee motivation by analyzing intrinsic and extrinsic motivational drivers. Using a qualitative approach, data were collected through in-depth interviews with employees and management personnel. The findings indicate that public service motivation remains a strong intrinsic driver, fostering employee commitment and engagement. However, extrinsic factors, including leadership style, work environment, career advancement opportunities, and reward systems, also significantly impact motivation levels. Transformational leadership was found to enhance motivation by providing employees with a clear vision, recognition, and support. Conversely, bureaucratic constraints and excessive administrative burdens were identified as demotivating factors. The study highlights the importance of balancing intrinsic and extrinsic motivation through structured human resource policies, leadership development programs, and workplace improvements. The implications suggest that government institutions should adopt comprehensive strategies that integrate psychological and structural aspects of motivation to enhance employee satisfaction and productivity. Future research should explore the long-term effects of motivational strategies and compare public and private sector approaches to motivation. By addressing the identified motivational challenges, public institutions can improve employee performance and contribute more effectively to regional development.